Placing CF2 in the Center: Major Physicochemical Changes Upon a Minor Structural Alteration in Gem‐Difunctional Compounds. Issue 7 (12th December 2022) - Saphier, Sigal; Katalan, Shahaf; Yacov, Guy; Berliner, Anat; Redy‐Keisar, Orit; Fridkin, Gil; Ghindes‐Azaria, Lee; Columbus, Ishay; Pevzner, Alexander; Drug, Eyal; Prihed, Hagit; Gershonov, Eytan; et al.
Abstract: Fluorine atoms play an important role in all branches of chemistry and accordingly, it is very important to study their unique and varied effects systematically, in particular, the structure‐physicochemical properties relationship. The present study describes exceptional physicochemical effects resulting from a H/F exchange at the methylene bridge of gem‐difunctional compounds. The Δlog P (CF2‐CH2) values, that is, the change in lipophilicity, observed for the CH2 /CF2 replacement in various α, α‐phenoxy‐ and thiophenoxy‐esters/amides, diketones, benzodioxoles and more, fall in the range of 0.6–1.4 units, which for most cases, is far above the values expected for such a replacement. Moreover, for compounds holding more than one such gem‐difunctional moiety, the effect is nearly additive, so one can switch from a hydrophilic compound to a lipophilic one in a limited number of H/F exchanges. DFT studies of some of these systems revealed that polarity, conformational preference as well as charge distributions are strongly affected by such hydrogen to fluorine atom substitution. The pronounced effects described, are a result of the interplay between changes in polarity, H‐bond basicity and molecular volume, which were obtained with a very low 'cost' in terms of molecular weight or steric effects and may have a great potential for implementation in various fields of chemical sciences. Abstract : A large increase in lipophilicity is observed for CH2 /CF2 replacement in the center of di‐functional compounds. The increase, in the range of 0.6–1.4 units is for most cases, far above expected values. The effect is nearly additive, thus one can switch from a hydrophilic compound to a lipophilic one using a limited number of H/F exchanges. In this paper, the effect and its origins are explored.